The Combination of variety with cultural as well as chemical tactics reduce damage and yield loss caused by Helicoverpa armigera (Hubner) (Lepidoptere:Noctuidae), enhance agronomic performance and influence nodule formation in chickpeas - Fentahun, Zemenu; Mengesha, Getachew Gudero; Abera, Asnake; Boraysho, Biniam; Simion, Tariku (Journal of Scientific Agriculture, 2025)
Helicoverpa armigera is a key polyphagous insect that causes significant qualitative and quantitative chickpea yield reductions worldwide, including in Ethiopia. Field trials were conducted to assess the success of the combined effects of variety, cultural practices, and insecticide application to reduce damage and yield loss caused by H. armigera and improve nodulation and agronomic traits of chickpea around Arba Minch, southern Ethiopia, in 2022 and 2023. Eight treatments were arrayed in a completely randomized block design with three replicas. Dimtu variety maintained with insecticide sprays had the lowest mean number of larvae per plant (NLPP) after 72 hours of exposure (0.33), the number of damaged pods per plant (NDPP) (3.13) and the highest grain yield (2234.13 kg ha-1), which were statistically on par with Habru variety in the same manner. However, the highest number of effective nodules (NEN) (17.37) was noted from the Habru variety combined with trap cropping, which was statistically similar to the same variety combined with intercropping and the Dimtu variety combined with each intercropping and trap cropping. Control plots of both varieties exhibited the highest NLPP and NDPP and the lowest NEN and grain yields over the years. Insecticide sprays on Dimtu and Habru varieties reduced yield loss by 69.13% and 67.79% and increased yield advantage by 223.89% and 210.42%, respectively, over control plots. Economic analyses also confirmed that production of Dimtu and Habru varieties with insecticide spray resulted in superior net benefits (2775.80 and 2686.47 ha-1, respectively) and benefit-cost ratios (4.46 and 4.32, respectively) over control plots across years. Thus, employing the varieties Dimtu and partly Habru with insecticide spray exhibited the most efficient and cost-effective option in decreasing pest pressure, improving agronomic performance, reducing yield losses, and attaining maximum economic returns. So, it could be suggested for farmers in the study and other related areas to manage H. armigera and sustain chickpea productivity.